Pengaruh Pemahaman, Norma Subjektif dan Sanksi terhadap Kepatuhan Wajib Pajak UMKM di Kota Jepara dengan Kesadaran Wajib Pajak sebagai Variabel Intervening - Evi Jayanti; Trisni Suryarini (Universitas Batanghari, 2023)
This study aims to determine the effect of understanding, subjective norms and sanctions on MSME taxpayer compliance in Jepara City with taxpayer awareness as an intervening variable. In this study, the sample used was 100 samples of MSME actors in Jepara City using the slovin formula. This research uses simple random sampling method, distributing questionnaires and multiple linear regression. The results of this study indicate that tax understanding, subjective norms and taxpayer awareness have a positive effect on taxpayer compliance. While tax sanctions do not affect taxpayer compliance. Tax understanding has no effect on taxpayer awareness. However, subjective norms and tax sanctions have a positive effect on taxpayer awareness. Then, taxpayer awareness can mediate the effect of subjective norms and tax sanctions on taxpayer compliance but cannot mediate tax understanding.